The objectives of this research were to identify gender relation, communication channels and the use of agricultural information, to analyze the correlation between gender relation and communication channels, the correlation between communication channels and the use of agricultural information. The research was conducted in the Sub-District of Pacet, District of Cianjur and Sub-District of Megamendung, District of Bogor in the West Java Province. The research used a method of survey taking 134 - Krishnarini Matindas; Aida V.S. Hubeis; Amiruddin Saleh; Harsono Suwardi (Forum Pasca Sarjana, 2011)
The objectives of this research were to identify gender relation, communication channels and the use of agricultural information, to analyze the correlation between gender relation and communication channels, the correlation between communication channels and the use of agricultural information. The research was conducted in the Sub-District of Pacet, District of Cianjur and Sub-District of Megamendung, District of Bogor in the West Java Province. The research used a method of survey taking 134 samples of organic vegetable farmers consisting of 67 men and 67 women. The quantitative data was obtained from the questionnaires given to the farmers and supported by qualitative data collected by in-depth interviews. The research results indicate that men often used personal communication, but women seldom choose the personal channel. Both men and women seldom used the mass media channel. Both men and women often use agricultural information for themselves for practice and comparison but seldom for discussion with others. Men and women were both active in information seeking and discussing the received information, but in the control of agricultural information men were more dominant than women. Among women, the group had a significant relationship with information control, whereas among men the mass media had a significant correlation with information control. The agricultural information from a personal channel was used by men for themselves for the purpose of practice, comparison, discussion, or diffusion. However, among women, the agricultural information was used for comparison, discussion, and diffusion. The group channel omong men was used to diffuse agricultural information whereas among woman it was for comparison, discussion and diffusion. The agricultural information from the mass media was used by men for their own knowledge, comparison and diffusion. Women liked to discuss agricultural information with husbands and families. Key words: communication channels, access, control of agricultural information, gender